PERSPECTIVE BUILDING FOR DISASTER MANAGEMENT IN INDIA - R.R. Patil (European Scientific Journal, ESJ, 2015)
India is a country vulnerable to number of natural and human made disasters. Its 58.6% landmass prone to earthquakes; over 40 million hectares (12%) of land is prone to floods and river erosion; of the 7,516 km long coastline close to 5700 km is prone to cyclones and tsunamis; 68 per cent of the cultivable area is vulnerable to drought and hilly areas are at risk from landslides and avalanches. Similarly, vulnerability also exists due to Chemical, Biological, Radiological and Nuclear (CBRN) disasters. In order to deal with varied nature of disaster the Government of India has adopted policy document and legislation on disaster management in 2005. The government approach to disaster has changed from ‘reactive approach’ to ‘pro-active approach’. In this context, the present paper takes overview of disaster management practice in India. It tried to highlight relevance of perspective building for disaster management and proposing antidiscriminatory perspective for disaster management as potential framework for intervention during the natural as well as human-made disasters. The present paper is divided into three parts; Part one explains the need of perspectives building for disaster management, Part, two discusses about the anti-discriminatory perspective for disaster management, and part three highlights importance of anti-discriminatory approach in the post disaster and its implications for human service as well as social work disciplines.